Bidirectional relationship between child language development and social skills across early childhood: Influences on later socio-emotional outcomes - Mensah, Fiona; Reilly, S; Reilly, Sheena; Mensah, F; Nicholson, J; Nicholson, Jan Maree; Westrupp, E; Westrupp, Elizabeth Mary (My University, 2015)
Objective: Many studies have identified comorbidity between child language problems and social difficulties, though few have assessed causality; it therefore remains unclear whether language problems cause social difficulties, or vice versa. The current study aims to more precisely document the nature and direction of the relationship between children’s development of vocabulary skills and social development (prosocial skills and peer difficulties) across early childhood, and the influence of each on later emotional and behavioural outcomes. Method: We used cross-lagged path analysis with three waves of nationally representative survey data from the Longitudinal Study of Australian children, for two cohorts of children (N>3000 each), aged 4-5, 6-7 and 8-9 years at each wave. Vocabulary was assessed using the Peabody Picture Vocabulary Test (PPVT) and social development was assessed using the Prosocial Skills and Peer Problems subscales of the Strengths and Difficulties Questionnaire. Two models tested the bidirectional relationship between (a) vocabulary and pro-social skills and (b) vocabulary and peer problems. Results: We found evidence for bidirectional effects. In the first model, vocabulary skills at age 4-5 years predicted peer problems at age 6-7 years, while peer problems at age 4-5 predicted vocabulary skills at age 6-7. Similarly, in the second model, vocabulary skills at age 4-5 years predicted prosocial skills at age 6-7 years, and vice versa. In both models these effects were no longer evident between ages 6-7 and 8-9 years. Future analysis will examine how these bidirectional effects relate to later socio-emotional and outcomes. Conclusions: Our findings suggest that there are bidirectional effects between language and social development, which are stronger when children are younger and reduce over time. These results provide support for early intervention and highlight the need for dual-assessment of language and social development for children presenting to early childhood services.
Keywords: Child Development -- Emotional; Child Development -- Speech and Language; Childhood and child development; Child Development; Emotional; Speech and Language; Childhood and child development